1997
DOI: 10.1111/j.1600-9657.1997.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

A histological and quantitative histomorphometric study of apexification of nonvital permanent incisors of vervet monkeys after repeated root filling with a calcium hydroxide paste

Abstract: The purpose of this study was to compare the effect of a monthly refilling of the root canals with calcium hydroxide paste with a single packing or replacement of the paste at 3 months on the apexification of nonvital maxillary incisors of vervet monkeys. Forty-eight maxillary incisors from 12 monkeys were used following radiographic determination that root development was incomplete. The pulps were extirpated under general anesthesia and the root canals filed and cleaned. The root canals were filled with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 6 publications
2
26
1
3
Order By: Relevance
“…Due to wide apical foramen diameter and the presence of exudate in the periapical region, dressing dissolution rate increases, thereby creating the need for change. 21,22 The present study agrees with the following authors when suggesting to keep intracanal dressing inside the root canal for much longer periods without periodic changes: Chosack et al, 23 Felippe et al, 28 Steiner et al, 29 Chawla et al 33 and Túrkún. 36 The study conducted by Chawla 33 found mineralized tissue formation after intracanal dressing remained in the root canal for 6 to 12 months without periodic changes.…”
Section: Discussionsupporting
confidence: 81%
“…Due to wide apical foramen diameter and the presence of exudate in the periapical region, dressing dissolution rate increases, thereby creating the need for change. 21,22 The present study agrees with the following authors when suggesting to keep intracanal dressing inside the root canal for much longer periods without periodic changes: Chosack et al, 23 Felippe et al, 28 Steiner et al, 29 Chawla et al 33 and Túrkún. 36 The study conducted by Chawla 33 found mineralized tissue formation after intracanal dressing remained in the root canal for 6 to 12 months without periodic changes.…”
Section: Discussionsupporting
confidence: 81%
“…Chawla (6) has suggested that the amount of CaOH in the single root canal dressing was sufficient to initiate and complete the bridge in 92.3% of the teeth in his study. Chosack et al (12) suggested that repeated root filling are not required as CaOH is only required to initiate healing process. They also reported that the CaOH has to be replaced if there are any symptoms or displacement of the medicament.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested time to change the CH in the canal varies from once every 3 months, once every 6-8 months, or not at all (31)(32)(33).…”
Section: Treatment Outcomesmentioning
confidence: 99%